Akhlak In Public Spaces (Highways) and Its Social Impacts (Humanism-Religious Perspective) - Sukino Sukino (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This article explains morality in the public sphere and its social impact on modern society. Public space becomes a free area so that social control is low when used. Through ethical understanding and awareness in the public sphere, human freedom in the perspective of humanism moves in line with the meaning that humans are created as a blessing for all nature. The method of this study is a literature review of the concept of morality in the public sphere and religious humanism as a perspective to find meaning. The results of this literature review are. First, the main morals in the public space which have implications for modern people's lives, such as occupying empty spaces in the taillight, opening road spaces, providing valid information and fixing road directions, not throwing garbage, not joking, and not making tents—street stage. Second, through the perspective of religious humanism, morality in the public sphere provides essential meanings in life, namely: saving lives, providing happiness, maintaining quality life, and humanist education.